Homesickness, Anxiety and Depression among Pakistani International Students in Indonesia during Covid-19 Outbreak - Shahzad Shoukat; Cyuzuzo Callixte; Theresia Indah Budhy; Jusak Nugraha; Tuyishimire Irene (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: International students are exposed to multiple mental health crisis due to social, environmentaland culture shocks in foreign lands but it gets worse in presence of life- threatening disease outbreak. Thisresearch was conducted to evaluate the homesickness, anxiety and depression among Pakistani internationalstudents in Indonesia during Covid-19 Outbreak. Methods: This study was conducted on 86 randomstudents that are pursuing their studies in different public and private universities in Indonesia. The datawere collected by distributing google forms via email and social media groups and the responses fromthe respondents were recorded and analyzed statistically. Results: The study findings revealed that thereis a correlation between Covid-19 pandemic and the development of various mental health crisis where33 students (38.37 %) developed homesickness, 11 students (12.79%) developed anxiety and 2 students(2.33 %) manifested low-grade depression. Homesickness was outstandingly observed in females (72.72%) whereas anxiety was highly reported in males (90.90%).The study findings demonstrated that there isa strong negative correlation between student financial statuses and the development of homesickness (r:-0.977, P: 0.023) and anxiety (r: -0.944, P: 0.056).Conclusion: All in all, the fear to contract coronavirus,lockdowns, financial instability, death toll of citizens and medical professionals, run out of medical facilitiesand social media hoaxes are significant risk factors of mental health crisis among Pakistani internationalstudents in Indonesia.